Digital Flash Card Media for Early Reading Learning in Elementary Schools - Nur Azmi Alwi; Desi Aulia (Universitas Pendidikan Ganesha, 2023)
Many students need to learn the letters correctly, often make mistakes in distinguishing letters that are almost similar in shape, have difficulty, and are not fluent in reading. For this reason, teachers need to develop learning media that can attract students' interest, are practical to use, digital-based, and are by student characteristics and technological developments so that learning to read becomes fun. This study aimed to develop digital Flash Card media in early reading learning in elementary schools. The subjects in this study were first-grade students, totaling 30 students. The research method used is the method of research and development or Research and Development (R&D). Data collection was carried out through interviews, questionnaires, and observation. The collected data were analyzed using qualitative and quantitative descriptive analysis techniques. The results showed that the validation test for digital Flash Card media products by material experts was 87% in a very valid category. The assessment by media experts is 90% with a very valid category, and an evaluation by linguists is 89% with a very valid type. Furthermore, the results of observing trials using digital Flash Card media on a large scale for elementary school students obtained an average of 87.7% in the practical category. It was concluded that the development of digital Flash Card media met the valid, helpful, and effective criteria for learning to read in elementary schools.